Medicine, money, and morals : physicians' conflicts of interest - Rodwin, Marc A. (Oxford University Press, 1995)
This is the first systematic examination of financial conflicts of interest in medicine. Marc Rodwin examines the evolution of those medical practices and institutions that left the profession open to conflicts of interest and makes clear suggestions for reform.